An Aligned Patterned Biomimetic Elastic Membrane Has a Potential as Vascular Tissue Engineering Material - Tan, Juanjuan; Bai, Jing; Yan, Zhiqiang (Frontiers in Bioengineering and Biotechnology, 2020)
Cardiovascular disease is the leading cause of death worldwide, with an annual mortality incidence predicted to rise to 23.3 million worldwide by 2030. Synthetic vascular grafts as an alternative to autologous vessels have shown satisfactory long-term results for replacement of large- and medium-diameter arteries, but have poor patency rates when applied to small-diameter vessels. Nanoparticles with low toxicity, contrasting agent properties, tailorable characteristics, targeted/stimuli- response delivery potential, and precise control over behavior (via external stimuli such as magnetic fields) have made possible their use for improving engineered tissues. Poly (styrene-block-butadiene-block-styrene) (SBS) is a kind of widely used thermoplastic elastomer with good mechanical properties and biocompatibility. Here, we synthesized anthracene-grafted SBS (SBS-An) by the method for the fabrication of a biomimetic elastic membrane with a switchable Janus structure, and formed the patterns on the surface of SBS-An under ultraviolet (UV) light irradiation. By irradiating the SBS-An film at different times (0, 10, 20, 30, 60, and 120 s), we obtained six well-ordered surface-patterned biomimetic elastic film with SBS-An at different heights in the thickness direction and the same distances of intervals (named sample-0, 10, 20, 30, 60, and 120 s). The structural effects of the SBS-An films on the adhesion and proliferation of human umbilical vein endothelial cells (HUVECs) were studied, and the possible mechanism was explored. When the HUVECs were cultured on the SBS-An films at different heights in the thickness direction, the sample-30 s with approximately 4 μm height significantly promoted adhesion of the HUVECs at the early stage and proliferation during the culture period compared with the samples of the lower (0, 10, and 20 s) and higher (60 and 120 s) heights. Consistent with this, the sample 30 s showed a higher stimulatory effect on the proliferation- and angiogenesis-related genes. These results suggest that SBS-An with appropriate height could efficiently control bioactivities of the biomimetic elastic membrane and might have great potential in vascular tissue engineering application.